Suicidality among bisexual youths: the role of parental sexual orientation support and concealment - Reyes, Marc Eric S (Archīum Ateneo, 2022)
Compared with the heterosexual population, the prevalence of mental health outcomes such as suicidality (suicidal ideation, suicide plans, and suicide attempts) is higher among sexual minority youth, particularly those who identify themselves as bisexuals. Bisexuals are at an even elevated risk within the LGB populations due to biphobia, monosexism, bisexual invisibility or erasure, and lack of support resources. These experiences may bring about issues regarding concealment of their sexual orientation linked to suicidality. Studies have also identified that parental support is a protective factor against suicidality among the youth, particularly their sexual orientation. The present study used a cross-sectional, predictive research design to examine parental sexual orientation support and concealment and their associations and predictive abilities in the suicidality of 151 Filipino bisexual youths aged 18–24 years old. The participants were recruited online within six months, from July 2021 to December 2021. As measured by the Parental Support for Sexual Orientation Scale, Sexual Orientation Concealment Scale, and Suicide Behaviors Questionnaire-Revised, results showed that among our bisexual participants, parental sexual orientation support and concealment did not have a significant relationship with and could not predict their risk for suicidality. Limitations and suggestions for further research were discussed, considering our findings.